Challenges facing otolaryngologists in low- and middle-income countries during the COVID-19 pandemic. (November 2020) - Kligerman, Maxwell P.; Lamour, Shaina; Okerosi, Samuel; ,; Alkire, Blake; Xu, Mary; Patterson, Rolvix; Fagan, Johan; Bhutta, Mahmood; Shrime, Mark; Gilles, Patrick Jean; Ibekwe, Titus; et al.
Abstract: The COVID-19 pandemic poses significant challenges for otolaryngologists practicing in low- and middle-income countries (LMICs). This commentary highlights some of the particular challenges in low resource settings, including limited testing, insufficient personal protective equipment, small numbers of surgeons, and competing socio-economic demands. The commentary focuses on specific examples from around the world to draw attention to these challenges and also highlight examples of success and innovation. Amidst the crisis an opportunity exists for otolaryngologists from around the world to share resources, ideas, and innovations to best serve patients and improve the health system globally for the future.